Mevalonic acid-dependent degradation of 3-hydroxy-3-methylglutaryl-coenzyme A reductase in vivo and in vitro - Correll, C.C.; Edwards, P.A. (The Journal of biological chemistry, 1994)
The microsomal enzyme 3-hydroxy-3-methylglutaryl-coenzyme A (HMG-CoA) reductase is subject to rapid degradation when cells are incubated with sterols or mevalonic acid (MVA). It has been shown that this rapid degradation is dependent upon both a sterol and another MVA-derived metabolite (Nakanishi, M., Goldstein, J. L., and Brown, M. S. (1988) J. Biol. Chem. 258, 8929-8937). In the current study, inhibitors of the isoprene biosynthetic pathway were used to define further this mevalonic acid derivative involved in the accelerated degradation of HMG-CoA reductase. The accelerated degradation of HMG-CoA reductase in met-18b-2 cells, which is induced by the addition of MVA, was inhibited by the presence of the squalene synthase inhibitor, zaragozic acid/squalestatin, or the squalene epoxidase inhibitor, NB-598. Accelerated degradation of HMG-CoA reductase was observed when NB-598-treated cells were incubated with both MVA and sterols. In contrast, the addition of MVA and sterols to zaragozic acid/squalestatin-treated cells did not result in rapid enzyme degradation. This MVA- and sterol-dependent degradation of HMG-CoA reductase persisted in cells permeabilized with reduced streptolysin O. Finally, the selective degradation of HMG-CoA reductase was also observed in rat hepatic microsomes incubated in vitro in the absence of ATP and cytosol. We conclude that the MVA-derived component that is required for the accelerated degradation of HMG-CoA reductase is derived from farnesyl disphosphate and/or squalene in the isoprenoid biosynthetic pathway. We propose that this component has a permissive effect and does not, by itself, induce the degradation of HMG-CoA reductase. We also conclude that the degradation of HMG-CoA occurs in the endoplasmic reticulum, and, once the degradation of HMG-CoA reductase has been initiated by MVA and sterols, all necessary components for the continued degradation of HMG-CoA reductase reside in the endoplasmic reticulum.